Resource dispersion and relatedness interact to explain space use in a solitary predator. Issue 8 (29th April 2020) - Aronsson, Malin; Åkesson, Mikael; Low, Matthew; Persson, Jens; Andrén, Henrik
Abstract : Resource dispersion or kin selection are commonly used to explain animal spatial and social organization. Despite this, studies examining how these factors interact in wild populations of solitary animals are rare. We used 16 years of individual‐level spatial and genetic data to disentangle how resources and relatedness influence spatial organization of a solitary predator, the Eurasian lynx Lynx lynx . As expected, space‐use overlap between neighbouring individuals increased when food resources were heterogeneous and unpredictably distributed (as predicted from resource dispersion) or when neighbours were closely related (as predicted from kin selection). However, these patterns were highly dependent on each other. Increased spatial overlap was restricted to mother–daughter dyads, with this effect only occurring in areas and during seasons when prey was clumped and irregularly distributed in the landscape. Additionally, full‐siblings with similar levels of genetic relatedness did not show these patterns, suggesting that kin selection is mediated through mother–daughter recognition, and is only beneficial under specific resource dispersion circumstances. Our results provide key insights into the flexibility of spatial organization of solitary animals, and clearly show the importance of considering the interaction between resources and kinship when assessing animal space use patterns.